Application of Andragogy-Based Simulation Method to Improving Digital Competence - Nurfadhilla, Mursyida; Ardiwinata, Jajat S; Saepudin, Asep (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This study aims to determine the application of andragogy-based simulations in improving digital marketing competence in whatsapp blaster training for waqf volunteers of the VIII batch of 2022 which took place at the AQL Islamic Center. The method used in this research is descriptive with a qualitative approach. Data was collected by direct observation, interviews and documentation studies. Testing the validity of the data is done by triangulation of sources, while the data analysis uses the techniques of reduction, display, and drawing conclusions. The results showed that 1) WhatsApp blaster training for waqf volunteers at AQL Islamic Center had implemented optimal simulation stages according to the steps in the learning method, seen from the learning process from beginning to end which was carried out during the training. 2) The implementation of the training uses an adult approach by taking into account the participants' self-concept, experience, readiness to learn from participants and learning orientation of participants. 3) There is an increase in digital marketing competence, especially in the whatsapp blaster material for the training participants, which is shown through the ability to broadcast whatsapp messages, the ability to increase database contacts, the ability to auto reply techniques and the ability to close consumer techniques.